A prospective evaluation of Dignity Therapy in advanced cancer patients admitted to palliative care. (May 2014) - Houmann, Lise J; Chochinov, Harvey M; Kristjanson, Linda J; Petersen, Morten Aa; Groenvold, Mogens
Background: Dignity Therapy is a brief, psychosocial intervention for patients with incurable disease. Aim: To investigate participation in and evaluation of Dignity Therapy and longitudinal changes in patient-rated outcomes. Design: A prospective (pre/post) evaluation design was employed. Evaluation questionnaires were completed when patients received the generativity document (T1) and 2 weeks later (T2). Changes from baseline (T0) were measured in sense of dignity, Structured Interview for Symptoms and Concerns items, Patient Dignity Inventory, Hospital Anxiety and Depression Scale and European Organisation for Research and Treatment of Cancer QLQ-C15-PAL (ClinicalTrials.gov number: NCT01507571). Setting/participants: Consecutive patients with incurable cancer, ≥18 years, informed of prognosis and not having cognitive impairment/physical limitations precluding participation were included at a hospice and a hospital palliative medicine unit. Results: Over 2 years, 80 of 341 eligible patients completed Dignity Therapy. At T1, 55 patients completed evaluations, of whom 73%–89% found Dignity Therapy helpful, satisfactory and of help to relatives; 47%–56% reported that it heightened their sense of purpose, dignity and will to live. Quality of life decreased (mean = −9 (95% confidence interval: −14.54; −2.49)) and depression increased (mean = 0.31 (0.06; 0.57)) on one of several depression measures. At T2 ( n = 31), sense of dignity (mean = −0.52 (−1.01; −0.02)) and sense of being a burden to others (mean = −0.26 (−0.49; −0.02)) improved. Patients with children and lower performance status, emotional functioning and quality of life were more likely to report benefit. Conclusions: This study adds to the growing body of evidence supporting Dignity Therapy as a valuable intervention in palliative care; a substantial subset of patients facing end of life found it manageable, relevant and beneficial.